Flexible thermal rectifier based on macroscopic PDMS@graphite composite film with asymmetric cone-shape interfaces - Chen, Bensong (2018)
Thermal rectifier is a device with the higher heat transport capacity in one direction than the backward one, being similar to the electrical diode working for the control of the electrical current. In this work, we report a new thermal rectifier based on the flexible macroscopic polydimethylsiloxane (PDMS) film with asymmetric cone-shape holes embedded with micrometer sized graphite powder (denoted as PDMS@graphite). The PDMS@graphite shows thermal rectification behavior with an extracted thermal rectification coefficient of 1.1326 ± 0.009 under 129.8 K temperature bias, and this value can be further modulated by changing the asymmetric ratio of the cone-shape interface in the PDMS@graphite film. Two underlying mechanisms are invited to explain the thermal rectification effect in the PDMS@graphite system. The one is the opposite temperature dependence of thermal conductivity for PDMS and graphite powder. The other one is the different temperature dependent thermal conductivity of the asymmetric cone-shape graphite in PDMS@graphite film in the forward and backward heating direction when applying the same temperature bias, which can be demonstrated in the COMOSL theoretical simulated temperature distributions for the PDMS@graphite. The as-fabricated flexible macroscopic PDMS@graphite composite film thermal rectifier may provide the potential applications in thermal control and management.